The Relationship between Solubility and Transdermal Absorption of Tadalafil - Hamed Hamishehkar; Mehdi Khoshbakht; Abolghasem Jouyban; Saeed Ghanbarzadeh (Tabriz University of Medical Sciences, 2015)
Purpose: The aim of this study was to find a relationship between drug solubility and its transdermal permeation and find the best vehicle composition to improve transdermal permeation of Tadalafil. Methods: Pure or binary mixtures of commonly used solvents in pharmaceutical sciences including ethanol, glycerin, N-methyl pyrrolidone (NMP), polyethylene glycol (PEG) 400 and propylene glycol (PG) were evaluated for drug solubility and transdermal delivery through the exercised rat skin employing Franz diffusion cells. Results: Tadalafil showed higher solubility in NMP compared to the other solvents. The amount of Tadalafil permeation from the pure vehicles was ranked as follow: Ethanol >glycerin >NMP>PEG 400 >PG. Furthermore, the solubility and transdermal delivery from binary mixtures of NMP and PG were higher than that obtained from pure PG, and accordingly, both increased with increasing NMP concentration in the binary solvent mixtures. The Flux values were determined as following order for Ethanol>NMP>glycerin>PG>PEG 400. Conclusion: Generally, increase in Tadalafil solubility resulted in a decrease in its skin penetration rate and amount. However, NMP exhibited substantial drug skin penetration rate and amount accompanying with appropriate drug solvency. In conclusion, the results of this study introduced NMP as a solvent suitable for application in the formulation of topically applied drug delivery systems.